Analysis of Differences in Financial and Market Performances That Do or Do Not Practice Income Smoothing - Prihatni, Rida; Ulupui, I Gusti Ketut Agung (E-Jurnal Akuntansi; Vol 33 No 4 (2023), 2023)
This study aims to examine differences in profitability, liquidity, leverage, stock returns, and share risk in real estate companies that do and do not practice income smoothing. The population of this study is companies publicly traded on the Indonesian Stock Exchange, from which sample of 32 companies was acquired for each of the three years of the study, giving 96 items in total. The indicators used in the study are return on assets (ROA) to measure profitability, current ratio (CR) to measure liquidity, debt-to-equity ratio (DER) to measure leverage, capital gains from stock prices to measure stock returns, and standard deviation of stock returns to measure stock risk. Analysis technique using independent samples t-testing and Mann-Whitney t-testing. The results of the study show that there is no difference in ROA, CR, DER, stock returns, and share risk between income-smoothing and non-income-smoothing companies. Keywords: Return on Assets; Current Ratio; Debt-to-Equity Ratio; Stock Return; Stock Risk; Income Smoothing